Congenital nasal neuroglial heterotopia and encephaloceles: An update on current evaluation and management. (13th January 2016) - Adil, Eelam; Robson, Caroline; Perez‐Atayde, Antonio; Heffernan, Colleen; Moritz, Ethan; Goumnerova, Liliana; Rahbar, Reza
Abstract : Objectives/Hypothesis: To describe our experience and current management approach for congenital nasal neuroglial heterotopia (NGH) and encephaloceles. Study Design: Retrospective chart review at a tertiary pediatric hospital from 1970 to 2013. Methods: Thirty patients met inclusion criteria: 21 NGH and nine encephaloceles. Data including demographics, pathology, imaging modality, surgical approach, resection extent, outcomes, and complications were analyzed. Results: Fourteen NGH patients (67%) presented with an internal nasal mass and nasal obstruction. Three patients (14%) presented with an external nasal mass and four (19%) had a mixed lesion. Median age at surgery was 0.51 years (interquartile range 1.32 years). Thirteen (62%) had an intranasal endoscopic approach. Median operative time was 1.6 hours (interquartile range 1.2 hours), and there were no major complications. Nine patients with encephalocele were identified: six (67%) presented with transethmoidal encephaloceles, two (22%) presented with nasoethmoidal encephaloceles, and one (11%) presented with a nasofrontal lesion. The median age at surgery was 1.25 years (interquartile range 1.4 years). All patients required a craniotomy for intracranial extension. Median operative time was 5 hours (interquartile range 1.9 hours), and eight patients (88%) had a total resection. Length of stay ranged from 3 to 14 days. Conclusion: Nasal neuroglial heterotopia and encephaloceles are very rare lesions that require multidisciplinary evaluation and management. At our institution, there has been a shift to magnetic resonance imaging alone for the evaluation of NGH to avoid radiation exposure. Endoscopic extracranial resection is feasible for most intranasal and mixed NGH without an increase in operative time, residual disease, or complications. Level of Evidence: 4. Laryngoscope, 126:2161–2167, 2016